COASTAL FLOODING: DAMAGE CLASSIFICATION AND CASE STUDIES IN CALABRIA, ITALY - Nucera, Antonella; Foti, Giandomenico; Canale, Caterina; PUNTORIERI, PIERFABRIZIO; Minniti, Francesca (WIT Transactions on Engineering Sciences, 2018)
Coastal flooding is a topic of particular interest both in scientific research and for public administration. In fact, effective management of both coastal erosion and coastal flood risk requires a mapping of flooding areas by current European legislation (Directive 2007/60/EC). Regarding Italy, coastal erosion is widely studied and mapped, but coastal flooding has not been uniformly examined across all regions. This paper analyses the main factors that influence coastal flooding, being mainly tidal excursion and run-up, and a new methodology is proposed for the classification of storm damage based on the effects produced by the coastal wave action. In fact, six classes of damage have been defined, sorted by increasing severity, namely: traffic interruption, infrastructure damage, maritime works damage, erosion of beaches and dunes, flooding to homes, and a combination of these various factors. The new classification was applied to two case studies, both in Calabria (Italy): Scilla on the Tyrrhenian coast, and Monasterace on the Ionian coast. The two locations were chosen because in Scilla the coastal morphology makes it particularly subject to storms that overreach the beach and reach local houses, even those located upstream of the seafront. In Monasterace, on the other hand, there is an important archaeological site on a coastal dune that, over the years, has often been damaged by sea storms. The analysis of the events was conducted starting with data present in the A.Si.Cal. (Historically flooded areas in Calabria) of the CNR-IRPI of Cosenza, which containing data relating to events of hydrogeological instability, including sea storms which have occurred in Calabria over the last few centuries, and from the MeteoCean group of the University of Genoa, which contains wave data for the period 1979–2017, which is reconstructed from the Climate Forecast System Reanalysis (CFSR) data.